Observation of Royle’s Pika (Ochotona roylei) in Api Nampa Conservation Area, Far Western Region, Nepal - Koju, Narayan P; Chalise, Mukesh Kumar (Journal of Natural History Museum, 2015)
This study was carried out on the southern base of Mt. Api in Api Nampa Conservation Area (ANCA) during June of 2012 and 2013. Pikas were observed for their population and behaviors. Feeding behavior was observed on more than 23 plants species including poisonous species to cattle. Pikas raid the human supply sometime peeping into human shelter. Local people use pika meat to cure some diseases. J. Nat. Hist. Mus. Vol. 27, 2013: 78-86